Post-synthetic cation exchange in the robust metal-organic framework MIL-101(Cr) - Szilagyi, Petra; Serra-Crespo, P.; Dugulan, I.; Gascon, J.; Geerlings, H.; Dam, B. (The Royal Society of Chemistry, 2013)
In this work an unambiguous proof of post-synthetic solvent-assisted cation exchange in the robust metal-organic framework MIL-101(Cr) is reported. Such substitution can alter directly the secondary building unit, which often defines the properties of the material.